Metabolomics of small extracellular vesicles derived from isocitrate dehydrogenase 1-mutant HCT116 cells collected by semi-automated size exclusion chromatography - Hayasaka, Ryosuke; Tabata, Sho; Hasebe, Masako; Ikeda, Satsuki; Hikita, Tomoya; Oneyama, Chitose; Yoshitake, Jun; Onoshima, Daisuke; Takahashi, Kumiko; Shibata, Takahiro; Uchida, Koji; Baba, Yoshinobu; et al. (Frontiers in Molecular Biosciences, 2023)
Cancer-derived small extracellular vesicles (sEVs) are multifunctional particles with a lipid bilayer structure that are involved in cancer progression, such as malignant proliferation, distant metastasis, and cancer immunity evasion. The separation protocol used to isolate sEVs is an important process and thus, several have been developed, including ultracentrifugation (UC), size exclusion chromatography (SEC), and affinity purification using antibodies against sEV surface antigens. However, the effects of different separation methods on sEV components have not been adequately examined. Here, we developed a semi-automated system for collecting sEVs by combining SEC and preparative high-performance liquid chromatography and applied it to metabolome analysis. The developed SEC system could recover sEVs more efficiently and non-destructively than UC, suggesting that it is an appropriate recovery method for metabolic analysis and reflects biological conditions. Furthermore, using the developed SEC system, we performed metabolome analysis of sEVs from isocitrate dehydrogenase 1 (IDH)-mutated human colon HCT116 cells, which produce the oncogenic metabolite, 2-hydroxyglutaric acid (2-HG). IDH1-mutated HCT116 cells released significantly more sEVs than wild-type (WT) cells. The metabolomic profiles of IDH1 mutant and WT cells showed distinct differences between the cells and their sEVs. Notably, in IDH mutant cells, large amounts of 2-HG were detected not only in cells, but also in sEVs. These results indicate that the SEC system we developed has wide potential applications in sEVs research.